2021
DOI: 10.1155/2021/8231559
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin Expression in the Development of Myocardial Hypertrophy

Abstract: Background. Expression of cholecystokinin is found in myocardial tissues as a gastrointestinal hormone and may be involved in cardiovascular regulation. However, it is unclear whether there is an increase in cholecystokinin expression in myocardial hypertrophy progression induced by abdominal aortic constriction. The study is aimed at exploring the relationship between cholecystokinin expression and myocardial hypertrophy. Methods. We randomly divided the 70 Sprague-Dawley rats into two groups: the sham operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…MH animal can be established in several mammal species (Roth et al 2017;Fu et al 2020;Han et al 2021), but mice are widely used because of their complete genetic background information, abundant commercial reagents, economical maintenance and easy feeding. Mice models of transverse aortic constriction (TAC) respond to post-load stress by initiating a series of altered gene expressions and activating complex crosstalk between signal pathways (Zhao et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…MH animal can be established in several mammal species (Roth et al 2017;Fu et al 2020;Han et al 2021), but mice are widely used because of their complete genetic background information, abundant commercial reagents, economical maintenance and easy feeding. Mice models of transverse aortic constriction (TAC) respond to post-load stress by initiating a series of altered gene expressions and activating complex crosstalk between signal pathways (Zhao et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cholecystokinin (CCK) is a classical gut hormone and a potent stimulator of gallbladder contraction that was found in extracts of small intestinal mucosa in the 1920s [ 8 , 9 ]. Subsequently, CCK has also been found in neurons [ 10 ], immune cells [ 11 ], kidney cells, and lung cells [ 12 ]. Pro-CCK is processed into several molecular forms such as CCK-58, CCK-33, CCK-22, CCK-8, and CCK-4; however, sulfated carboxyl-terminal CCK octapeptide (CCK-8) is the major biological active fragment of CCK, which retains most of the bioactivities of CCK.…”
Section: Introductionmentioning
confidence: 99%
“…Pro-CCK is processed into several molecular forms such as CCK-58, CCK-33, CCK-22, CCK-8, and CCK-4; however, sulfated carboxyl-terminal CCK octapeptide (CCK-8) is the major biological active fragment of CCK, which retains most of the bioactivities of CCK. Two types of receptors for CCK (CCK 1 receptor (CCK 1 R) and CCK 2 receptor (CCK 2 R)) have been classified as belonging to the G protein-coupled receptor superfamily (GPCRs) and its distribution is tissue-dependent [ 12 14 ]. Recently, it has been demonstrated that pro-CCK, CCK, and its receptors are expressed in mammalian cardiomyocytes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation